Model Pengasuhan Alternetif Dual-Career Family dalam Pemenuhan Kebutuhan Asuh - Hanik, Elya Umi; Nawafilaty, Tawaduddin (Association of Indonesian Islamic Kindergarten Teachers Education Study Program, 2018)
Taking care of children shows to way that selected by parents in educating and taking care of their children. In the practice, it includes taking care of eating, drinking, outfit, home and making sure the success of childrens? development and growth until they become adult. Family becomes respondent in this research including husband-wife which the wife is lecturer and the husband is entrepreneur and teacher, civil servant and private. Data acquired from observation and deep interview. The researcher limits the research on subject with dual-career criteria who has 0-8 year child. The taking care meant here shows on certain ways did by parents in fulfilling childrens? base needs. The result of this research is hoped to be additional references in construction of parenting theory according to families? characteristics in which the mother works in University at Lamongan Regency, and Indonesia families generally.